2004
DOI: 10.1074/jbc.m402194200
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α and CD80 Modulate CD28 Expression through a Similar Mechanism of T-cell Receptor-independent Inhibition of Transcription

Abstract: Replicative senescence of human T cells is characterized by the loss of CD28 expression, exemplified by the clonal expansion of CD28null T cells during repeated stimulation in vitro as well as in chronic inflammatory and infectious diseases and in the normal course of aging. Because CD28 is the major costimulatory receptor for the induction of T cell-mediated immunity, the mechanism(s) underlying CD28 loss is of paramount interest. Current models of replicative senescence involve protracted procedures to gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 62 publications
3
35
0
Order By: Relevance
“…Consistent with previous findings showing a direct repressive effect of TNF␣ on CD28 gene transcription (26,27), we found that exposure of patient-derived T cells to TNF␣ in vitro consistently resulted in the further down-regulation of CD28 (Figure 3B), showing that T cells in RA patients are responsive to TNF␣. Consistent with previous reports that TNF␣ down-regulates expression of its own receptors (33,39), our data show that T cells have decreased numbers of TNFRI and TNFRII molecules that correspond with a quantitative decrease of CD28 molecules in response to TNF␣ in vitro ( Figure 3B).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous findings showing a direct repressive effect of TNF␣ on CD28 gene transcription (26,27), we found that exposure of patient-derived T cells to TNF␣ in vitro consistently resulted in the further down-regulation of CD28 (Figure 3B), showing that T cells in RA patients are responsive to TNF␣. Consistent with previous reports that TNF␣ down-regulates expression of its own receptors (33,39), our data show that T cells have decreased numbers of TNFRI and TNFRII molecules that correspond with a quantitative decrease of CD28 molecules in response to TNF␣ in vitro ( Figure 3B).…”
Section: Discussionsupporting
confidence: 92%
“…The dynamic changes in CD28 expression on CD4ϩ T cells have also been shown by other investigators to correlate with the clinical course of disease activity (44). Therefore, if such changes in the in vivo expression levels of CD28 are indeed coupled with the dysregulation of TNF␣ in RA (26)(27)(28), then anti-TNF␣ therapy (45)(46)(47) could also have an impact on CD28 expression. Our data show a significant trend toward an increase in the number of CD28 molecules in patients posttreatment (Figure 4).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…These results are predictable, since CD28 is highly sensitive to down-modulation following cellular activation (19,20). Extraarticular RA confers an increased burden of inflammation, with overexpression of endothelial HLA-DQ and IL-1, and with high serum levels of TNF␣ (34,35) known to directly inhibit CD28 gene transcription (13,25). Systemic inflammation and endothelial activation suggest an environment permissive of chronic T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…The T cell line JT is a Jurkat derivative that has low-to-nil expression of CD28 (25). In empirical studies, JT was found to express CD56 when incubated overnight with 50 ng/ml phorbol myristyl acetate (Sigma-Aldrich, St. Louis, MO), and it maintained a high expression level of CD56 for at least 2 days in the absence of phorbol myristyl acetate.…”
Section: Methodsmentioning
confidence: 99%